Islam Liberal dan Rasional: Kajian Atas Pemikiran Syed Ameer Ali - Alimuddin Hassan Palawa (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2002)
This paper presents an overview of Syed Ameer Ali’s perspectives on the causes behind the rise and decline of classical Islamic civilization. It further examines several of his key liberal-rational ideas, focusing on three main topics: (i) polygamy in Islam, (ii) slavery in Islam, and (iii) eschatological life in Islam. To provide context, this study begins with a brief biographical account of Syed Ameer Ali before delving into his intellectual contributions.